Structural factors affecting Asians and Pacific Islanders in community-based substance use treatment: Treatment provider perspectives. Issue 4 (2nd October 2017) - Chang, Jamie Suki; Sorensen, James L.; Masson, Carmen L.; Shopshire, Michael S.; Hoffman, Kim; McCarty, Dennis; Iguchi, Martin
ABSTRACT: Asians and Pacific Islanders (API) have large disparities in utilization of substance use treatment compared to other racial groups. In this study, we analyzed factors that shape API experiences accessing and engaging in community-based treatment from the perspective of treatment providers. We conducted semi-structured interviews with 40 treatment providers who work with API clients in treatment programs in San Francisco and Los Angeles. We analyzed the transcribed interview data in ATLAS.ti using a content analysis approach. There were three main findings. First, treatment providers found the API category itself is too broad and heterogeneous to meaningfully explain substance use patterns. Second, beyond race/ethnicity, structural factors such as poverty, neighborhood, housing, and age had an impact on API substance use. Third, factors such as family, immigration status, religion, language, stigma played complex roles in API treatment experiences, contingent on how client, programs, and providers attended to differences in these categories.